VD_FINDINFO HC / 2012 / 92 vom 8. November 2011 - VD Tribunal cantonal (2011)
RÉSILIATION ABUSIVE, CONTRAT DE TRAVAIL, HEURES DE TRAVAIL SUPPLÉMENTAIRES | 337 CO, 337d al. 1 CO, 308 CPC (CH), 310 CPC (CH), 313 CPC (CH), 405 CPC (CH)